Interfacial engineering of a thiophene-based 2D/3D perovskite heterojunction for efficient and stable inverted wide-bandgap perovskite solar cells. (December 2021) - Chen, Cong; Liang, Jiwei; Zhang, Junjun; Liu, Xinxing; Yin, Xinxing; Cui, Hongsen; Wang, Haibing; Wang, Chen; Li, Zaifang; Gong, Junbo; Lin, Qianqian; Ke, Weijun; et al.
Abstract: Fabricating highly efficient and stable inverted wide-bandgap (WBG) perovskite solar cells (PSCs) is the key factor for developing high-efficiency and stabilized tandem solar cells. Herein, we propose an interfacial engineering strategy to form a 2D/3D perovskite heterojunction using 2-thiopheneethylammonium chloride (TEACl). The thiophene-based 2D/3D perovskite heterojunction improves the optoelectronic properties of the perovskite absorber, passivates the electron and hole traps, increases the activation energy of the ion movement, and lowers the dark saturation current density of the device. As a result, the device with TEACl treatment delivers a champion power conversion efficiency of 20.31% with a 1.68-eV bandgap. In addition, the devices with TEACl treatment exhibit superior stability than the control devices under various testing conditions. Finally, an efficiency of 24.0% is achieved for a 4-terminal perovskite/CIGS tandem solar cell. Our results demonstrate that the thiophene-based 2D/3D perovskite heterojunction is a promising approach for achieving efficient and stable WBG PSCs. Graphical Abstract: A thiophene-based 2D/3D perovskite heterojunction interface is developed for wide-bandgap perovskite solar cells to promotes the efficiency to 20.31% with a high V OC of 1.19 V and demonstrates superior stability under harsh conditions. ga1 Highlights: Find a new interfacial passivator TEACl to enhance the device performance of 1.68-eV wide-bandgap PSCs. Achieve an efficiency of 24.0% for a 4-T perovskite/CIGS tandem solar cell. Demonstrate the universality and significance of 2D/3D heterojunction for highly efficient and stable PSCs.